Remark on algorithm 705 A Fortran-77 software package for solving the Sylvester matrix equation AXBT + CXDT = E. - Hopkins, Tim (ACM transactions on mathematical software.)
We present a number of corrections to Algorithm 705 [Gardiner et al. 1992].